2022
DOI: 10.3390/civileng3010010
|View full text |Cite
|
Sign up to set email alerts
|

Greening Roadway Infrastructure with Vetiver Grass to Support Transportation Resilience

Abstract: With flooding and other weather events intensifying, more cost-effective erosion and flood control systems are needed. Vetiver (Chrysopogon zizanioides (L.) Roberty), is part of an arsenal of sustainable, low cost, and green infrastructure tools to reduce the risks of erosion, landslides, and flooding. This study investigates vetiver and its broader application to transportation planning. Based on a literature review and interviews with experts, vetiver as a green infrastructure tool is summarized. An evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…With this guide, further research was conducted to identify potential areas that would be benefit from green infrastructure or nature-based transportation solutions. The research team investigated and developed a framework for the use of vetiver grass—Chrysopogon zizanioides (L.) Roberty—as a cost-effective control and mitigation solution to reduce erosion, landslides, and flooding along the transportation corridors of Kuhio Highway ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…With this guide, further research was conducted to identify potential areas that would be benefit from green infrastructure or nature-based transportation solutions. The research team investigated and developed a framework for the use of vetiver grass—Chrysopogon zizanioides (L.) Roberty—as a cost-effective control and mitigation solution to reduce erosion, landslides, and flooding along the transportation corridors of Kuhio Highway ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study by [43] examined combining biochemical surface treatments with vegetation and found that using seeded biochemical treatments on slopes was effective for both short-and long-term stabilization against erosion. Recent work by [44] highlighted the potential for vetiver grass to support resilient transportation systems by mitigating slope failures and improving stormwater quality, but this study also highlighted the relative lack of use of vetiver in the United States.…”
Section: Introductionmentioning
confidence: 93%
“…The leaves of this plant have also been used to remove parasitic infections in feed animals [131], and the mixture of its roots and leaves has been used as a pain reliever for rheumatoid arthritis, lumbago, and sprain [126]. Recently, the utility of vetiver grass as a green infrastructure tool for transportation planning to reduce the risks of erosion, landslides, and flooding was reported [132].…”
Section: Traditional and Medicinal Uses Of Vetiver Grassmentioning
confidence: 99%